Economic Value A Dried Fish Business Development in Bengkulu City - Bambang Sumantri; Agus Purwoko; Sriyoto; Ketut Sukiyono; Eko Sumartono (Talenta Publisher, 2018)
The study aims to analyze the economic value of dried fish business by considering its added value of Hayami and marketing. This study uses primary data by surveying 55 dried fish producers in Bengkulu city. The results show that the average output price of dried fish is Rp6,586.61/kg. Using formula of Hayami’s added value, the average added value gained is Rp3,486.14/kg. This informs that every a kilogram of fresh fish processed into dried fish will create added value of Rp3,486.14. When labor under consideration, labor added value in fish dried industries is Rp651.37 informing that an average of labor income for every kilogram of fish dried produced. The research also found that there are four patterns of marketing channels. From weekly average production of dried fish, i.e., 4,345 kg, 43.73 % is distributed to big traders while the remaining, 56.27%, is consumed directly. From big traders, dried fish are then distributed through three channel, namely, (1) 43.11 % are marketed to the first intermediate trader, then, to intercity merchants, retailers and end customers in Bengkulu city, (2) 26.32% are distributed to second intermediate trader who then marketed to retailers and end customers; and (3) 31.58 % are marketed to third intermediate trader who, then, market to the intercity merchants and consumers. Marketing margins of this dried fish is Rp1,000/kg from producers to traders and Rp2,000/kg per kg of fish from traders to retailers.